The future: medical advances in MEN1 therapeutic approaches and management strategies. Issue 10 (October 2017) - van Leeuwaarde, Rachel S; de Laat, Joanne M; Pieterman, Carolina R C; Dreijerink, Koen; Vriens, Menno R; Valk, Gerlof D
Abstract : Multiple endocrine neoplasia type 1 is a rare autosomal inherited disorder associated with a high risk for patients to simultaneously develop tumors of the parathyroid glands, duodenopancreatic neuroendocrine tumors and tumors of the anterior pituitary gland. Early identification of MEN1 in patients enables presymptomatic screening of manifestations, which makes timely interventions possible with the intention to prevent morbidity and mortality. Causes of death nowadays have shifted toward local or metastatic progression of malignant neuroendocrine tumors. In early cohorts, complications like peptic ulcers in gastrinoma, renal failure in hyperparathyroidism, hypoglycemia and acute hypercalcemia were the primary causes of early mortality. Improved medical treatments of these complications led to a significantly improved life expectancy. The MEN1 landscape is still evolving, considering the finding of breast cancer as a new MEN1-related manifestation and ongoing publications on follow-up and medical care for patients with MEN1. This review aims at summarizing the most recent insights into the follow-up and medical care for patients with MEN1 and identifying the gaps for future research.